2018
DOI: 10.1186/s12974-018-1282-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction induces NLRP3 inflammasome activation during cerebral ischemia/reperfusion injury

Abstract: BackgroundNod-like receptor protein 3 (NLRP3) inflammasome is a crucial factor in mediating inflammatory responses after cerebral ischemia/reperfusion (I/R), but the cellular location of NLRP3 inflammasome in cerebral I/R has yet come to a conclusion, and there is still no specific evidence to state the relationship between mitochondria and the NLRP3 inflammasome in cerebral I/R.MethodsIn the present study, we detected the cellular localization of NLRP3 inflammasomes in a transient middle cerebral artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(173 citation statements)
references
References 43 publications
8
152
0
13
Order By: Relevance
“…Meng et al (2019) demonstrated that PPARÎł activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons. Further, NLRP3 inflammasome activation has been reported in microglia and neurons after OGD/reperfusion in vitro and during cerebral ischemia/reperfusion (Gong et al, 2018;Guo et al, 2018). Therefore, we speculated that NLRP3 inflammasome might be a promising therapeutic target for SCI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Meng et al (2019) demonstrated that PPARÎł activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons. Further, NLRP3 inflammasome activation has been reported in microglia and neurons after OGD/reperfusion in vitro and during cerebral ischemia/reperfusion (Gong et al, 2018;Guo et al, 2018). Therefore, we speculated that NLRP3 inflammasome might be a promising therapeutic target for SCI.…”
Section: Discussionmentioning
confidence: 86%
“…NLRP3 inflammasome is assembled by NLRP3, ASC, and Caspase-1 after exogenous infection and endogenous signal stimulation; subsequently, there is Caspase-1 activation and the release of downstream inflammatory factors, such as IL-1β and IL-18 (Yan et al, 2015). Studies have reported NLRP3 inflammasome activation in microglia and neurons after oxygen-glucose deprivation (OGD)/reperfusion in vitro and in cerebral ischemia/reperfusion (Gong et al, 2018;Guo et al, 2018). There is post-SCI activation of NLRP3 inflammasome in an animal model involving microglia and spinal cord tissue (Grace et al, 2016;Jiang et al, 2016;Zendedel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although inflammasome signaling in the CNS is mainly attributed to microglia, the key innate immune cells of the brain, expression of inflammasome components has also been reported in other cell types of the CNS, including neurons (Kaushal et al , ), astrocytes (Freeman et al , ), perivascular CNS macrophages (Kawana et al , ), oligodendrocytes (Mckenzie et al , ), and endothelial cells (Gong et al , ) (Fig ). However, current understanding of inflammasome activation in microglia and its role in CNS inflammation and disease is still fragmentary and primarily based on in vitro studies with primary microglia and microglial cell lines, and in vivo studies with transgenic knockout mice that lack expression of specific inflammasome components throughout the body.…”
Section: Inflammasomes and The Central Nervous Systemmentioning
confidence: 98%
“…A cerebral ischemia reperfusion model was established using the tMCAO method [28], i.e., reperfusion for 24 h following ischemia for 2 h. Rats were intraperitoneally injected with 60 mg/kg pentobarbital sodium, following which the right common carotid artery, external carotid artery, and internal carotid artery were exposed. The silicone-coated MCAO filament (wire diameter: 0.28 mm; head diameter: 0.38 Âą 0.02 mm; and wire length: 45 mm) was inserted into the internal carotid artery through the external carotid artery incision and was directed to the start point of the anterior artery to block the blood flow to the middle cerebral artery.…”
Section: Cerebral Ischemia-reperfusion Modelmentioning
confidence: 99%